2016
DOI: 10.3174/ajnr.a4727
|View full text |Cite
|
Sign up to set email alerts
|

Performance of CT ASPECTS and Collateral Score in Risk Stratification: Can Target Perfusion Profiles Be Predicted without Perfusion Imaging?

Abstract: BACKGROUND AND PURPOSE: Endovascular trials suggest that revascularization benefits a subset of acute ischemic stroke patients with large-artery occlusion and small-core infarct volumes. The objective of our study was to identify thresholds of noncontrast CT-ASPECTS and collateral scores on CT angiography that best predict ischemic core volume thresholds quantified by CT perfusion among patients with acute ischemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…A recent study agreed with our conclusion. In this study, a cerebral blood flow core volume of 50 ml was evaluated, in which NECT-ASPECTS ≥9 with a CTA collateral score of 3 had 100% specificity for identifying patients with a cerebral blood flow core volume ≤50 ml 14 . Our data further showed that the combined interpretation of ASPECTS and collateral scores in agreement is superior to using higher cutoff values of ASPECTS or collateral scores in terms of both predictive capability and IRR.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study agreed with our conclusion. In this study, a cerebral blood flow core volume of 50 ml was evaluated, in which NECT-ASPECTS ≥9 with a CTA collateral score of 3 had 100% specificity for identifying patients with a cerebral blood flow core volume ≤50 ml 14 . Our data further showed that the combined interpretation of ASPECTS and collateral scores in agreement is superior to using higher cutoff values of ASPECTS or collateral scores in terms of both predictive capability and IRR.…”
Section: Discussionmentioning
confidence: 99%
“…Automated arterial input functions were automatically assigned by RAPID and could include either anterior or posterior circulation vessels. 26 MR Perfusion Imaging. MR perfusion images were obtained following an intravenous injection of gadolinium into an antecubital vein.…”
Section: Imaging Analysis Ct Perfusionmentioning
confidence: 99%
“…Though an NCCT ASPECTS score and CTA based collateral score may improve the CTP based candidate selection for revascularization (Dehkharghani et al, 2016) Single-phase computed tomography angiography (CTA) High accuracy in assessing the patency of the arterial segments in the circle of Willis and its anatomical variations.…”
Section: Non-contrast Computerized Tomography (Ncct)mentioning
confidence: 99%